MENS-associated increase of muscular protein content via modulation of caveolin-3 and TRIM72 - Ohno, Y; Egawa, T; Yokoyama, S; Fujiya, H; Sugiura, T; Ohira, Y; Yoshioka, T; Goto, K (Physiological research, 2019)
Microcurrent electrical neuromuscular stimulation (MENS) is known as an extracellular stimulus for the regeneration of injured skeletal muscle in sports medicine. However, the effects of MENS-associated increase in muscle protein content are not fully clarified. The purpose of this study was to investigate the effects of MENS on the muscular protein content, intracellular signals, and the expression level of caveolin-3 (Cav-3), tripartite motif-containing 72 (TRIM72) and MM isoenzyme of creatine kinase (CK-MM) in skeletal muscle using cell culture system. C2C12 myotubes on the 7th day of differentiation phase were treated with MENS (intensity: 10-20 microA, frequency: 0.3 Hz, pulse width: 250 ms, stimulation time: 15-120 min). MENS-associated increase in the protein content of myotubes was observed, compared to the untreated control level. MENS upregulated the expression of Cav-3, TRIM72, and CK-MM in myotubes. A transient increase in phosphorylation level of Akt was also observed. However, MENS had no effect on the phosphorylation level of p42/44 extracellular signal-regulated kinase-1/2 and 5'AMP-activated protein kinase. MENS may increase muscle protein content accompanied with a transient activation of Akt and the upregulation of Cav-3 and TRIM72.
Keywords: Muscle Fibers, Skeletal; myoblasty; Animals; Carrier Proteins; Electric Stimulation; kaveolin 3; elektrická stimulace; Muscle Proteins; Myoblasts; Mice; buněčné linie; transportní proteiny; svalové proteiny; Cell Line; Caveolin 3; kosterní svalová vlákna; myši; zvířata